2003
DOI: 10.1097/00006982-200312000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Focal Inner Retinal Hemorrhages in Patients with Drusen

Abstract: Superficial retinal hemorrhage in the paracentral area of patients with drusen is the earliest sign of OCRA and OCNV. Fluorescein angiography and indocyanine green angiography are important in detecting the dual nature of the subretinal neovascular network. Photocoagulation and photodynamic treatment is usually unsuccessful in preserving central vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(34 citation statements)
references
References 8 publications
3
30
0
1
Order By: Relevance
“…Finally, choroidal neovascularization occurs and forms retinal-choroidal anastomoses. In contrast, Gass et al [33] suggested that focal atrophy of the RPE and type 1 occult choroidal neovascularization under the RPE are the initial lesions of RAP. These lesions permit the retinal neovasculature to infiltrate into the outer retina and form chorioretinal anastomoses with the original type 1 occult choroidal vessel.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, choroidal neovascularization occurs and forms retinal-choroidal anastomoses. In contrast, Gass et al [33] suggested that focal atrophy of the RPE and type 1 occult choroidal neovascularization under the RPE are the initial lesions of RAP. These lesions permit the retinal neovasculature to infiltrate into the outer retina and form chorioretinal anastomoses with the original type 1 occult choroidal vessel.…”
Section: Discussionmentioning
confidence: 94%
“…The clinical forms of exudative AMD were divided into the following six categories using fluorescein angiography, SD-OCT scans and indocyanine green angiography if required: occult, minimally classic, predominantly classic, classic and type 3 CNV and idiopathic polypoidal vasculopathy as previously described [10,11,12,13,14,15,16]. The clinical forms were classified by two senior retina specialists (M.B.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown, for example, that ganglion cell neurites grow into human epiretinal membranes in association with glial cells [269,270]. There are also cases of intraretinal neovascularization which are permitted or induced by Müller cells: in patients with retinal angiomatous proliferation, a subform of exudative age-related macular degeneration, neovascularization starts in the outer plexiform layer, progresses to the subretinal space, and then anastomoses with choroidal vessels [271][272][273]. Multiple factors have been described to be involved in the formation and progression of epiretinal membranes which mediate their effects via autocrine and paracrine loops of different signaling molecules.…”
Section: Inhibitory Effects Of Müller Cellsmentioning
confidence: 99%